A new species of deep‐sea torquaratorid enteropneust (Hemichordata): A sequential hermaphrodite with exceptionally wide lips. Issue 3 (5th July 2022) - Holland, Nicholas D.; Hiley, Avery S.; Rouse, Greg W.
Abstract: Specimens of a new species of torquaratorid acorn worm (Hemichordata, Enteropneusta) were video recorded and subsequently collected at abyssal depths in the eastern North Pacific at sites ranging from Oregon to northern Mexico. These worms are described here as Yoda demiankoopi n. sp. by molecular and morphological methods. The new species differs from its only described congener, Yoda purpurata, in three ways. First, the lips are extremely wide and indented by a deep ciliary groove for ingesting substrate and conveying it to the mouth. Second, a connective tissue bulge of unknown significance runs mid‐dorsally along the hepatic and posthepatic regions of the intestine. Third, the posthepatic intestine is strikingly sinuous and packed with gut contents presumably undergoing digestion for extended periods between infrequent defecations. Yoda demiankoopi n. sp. is hermaphroditic, a character so far known only for the genus Yoda in the entire class Enteropneusta. The gonads of each adult worm comprise hundreds of ovaries (each containing a single oocyte) and hundreds of testes located just beneath the dorsal epidermis of the anterior trunk and associated genital wings. In any given animal, at any given time, gametes of only one sex or the other become fully mature. Thus, the worm is a sequential hermaphrodite, alternately spawning purely as a female or purely as a male.